A critical review on solvent extraction of rare earths from aqueous solutions - Xie, Feng; Zhang, Ting An; Dreisinger, David; Doyle, Fiona (Minerals engineering, 2014)
•Separation processes for RE solvent extraction from aqueous solutions have been reviewed.•Bastnesite, monazite, and xenotime are main sources of RE hydrometallurgical processing.•SX is the main technology to separate individual rare earths or produce mixed rare earths.•For process configuration, up to hundreds of stages of mixers and settlers may be used. Rare earth elements have unique physicochemical properties that make them essential elements in many high-tech components. Bastnesite (La, Ce)FCO3, monazite, (Ce, La, Y, Th)PO4, and xenotime, YPO4, are the main commercial sources of rare earths. Rare earth minerals are usually beneficiated by flotation or gravity or magnetic processes to produce concentrates that are subsequently leached with aqueous inorganic acids, such as HCl, H2SO4, or HNO3. After filtration or counter current decantation (CCD), solvent extraction is usually used to separate individual rare earths or produce mixed rare earth solutions or compounds. Rare earth producers follow similar principles and schemes when selecting specific solvent extraction routes. The use of cation exchangers, solvation extractants, and anion exchangers, for separating rare earths has been extensively studied. The choice of extractants and aqueous solutions is influenced by both cost considerations and requirements of technical performance. Commercially, D2EHPA, HEHEHP, Versatic 10, TBP, and Aliquat 336 have been widely used in rare earth solvent extraction processes. Up to hundreds of stages of mixers and settlers may be assembled together to achieve the necessary separations. This paper reviews the chemistry of different solvent extractants and typical configurations for rare earth separations.